Learning curve of microwave ablation for liver cancers. Issue 158 (January 2023) - Dou, Jianping; Yu, Jie; Cheng, Wen; Wei, Qiang; Luo, Yanchun; Han, Zhiyu; Cheng, Zhigang; Liu, Fangyi; Yu, Xiaoling; Liang, Ping
Abstract: Purpose: To evaluate MWA efficacy and safety by cumulative MWA volume and interventional experience. Method: 3113 primary liver cancers treated by 7 operators between 2006 and 2018 were studied. Conditional logistic regression was used to estimate within-operators effects of increasing cumulative MWA volume per year on major complication, technical efficacy (TE) and local tumor progression (LTP) rates were adjusted for treatment-level characteristics. Changes were also evaluated by subgroups of tumor size and location. Results: Lower severe complication rate was detected only in higher MWA volume (HR: 0.31, P = 0.02)). TE rates increased with the increase of MWA volume ((100–150 procedures (HR: 0.33, P = 0.00); 150–200 procedures (HR: 0.08, P = 0.00)) per year. Similar results were found in subgroup analysis of interventional experience (5 to < 10 years (HR: 0.10, P = 0.00). MWA volume per year larger than 150 cases could reduce the major complication rate for tumors smaller than 5 cm (HR: 0.21, P = 0.03) and tumors in higher risk location (HR: 0.18, P = 0.03). The increase of MWA volume per year could significantly increase the TE rate in all tumor size, expect for tumors in high-risk location (100–150 procedures (HR:1.12, P = 0.84), 150–200 procedures (HR: 0.14, P = 0.08)). Conclusions: Early and intensive performance of MWA procedures would reduce major complication rates regardless of tumor size and tumor location, but could not improve TE rate in high-risk locations.